Penerapan Metode Qowaid Dan Terjemah Pada Pembelajaran Bahasa Arab Di Pondok Pesantren Al Falah Puteri Banjarbaru - Aunia Ulfah; Nurhidayani; Muhammad Syukri (STIT Syekh Muhammad Nafis Tabalong, 2025)
Arabic language education in pesantren plays an important role in equipping students with strong language skills, especially in understanding religious texts. At Pondok Pesantren Al-Falah Puteri Banjarbaru, Arabic language learning still faces challenges in understanding grammar (Qowa’id) and the ability to translate texts. Therefore, effective methods are needed to improve the quality of Arabic language teaching at this pesantren. This research focuses on the application of the Qowaid an Translation method in Arabic language learning at Al- Falah Puteri Islamic Boarding School Banjarbaru. The main issues discussed are how the Qowaid and Translation method is implemented in Arabic language learning at the boarding school and the learning outcomes achieved by the students after the method is applied. This research employs a qualitative approach with a case study design. Data was collected through observation, interviews with teachers and students, and document analysis of the teaching materials used. Data analysis was performed through data reduction, presentation of data, and drawing conclusions. Research Results: The results of the study indicate that the application of the Qowa’id and Translation methods at Pondok Pesantren Al-Falah Puteri has proven effective in improving students' ability to understand Arabic grammar and translate texts. Overall, the implementation of these methods has had a positive impact on the students' mastery of the Arabic language. However, additional support methods are needed to ensure that students not only become proficient in Arabic grammar and translation but also become skilled in speaking Arabic fluently.